An Analysis of Types of English Sentences in English Folklore “Jack and the Beanstalk” from American Literature Website - Saragih, Dhea; Simangunsong, Tiara Indah Sari; Simanjuntak, Desy Natalia; Saragih, Roma Rezeki Nami; Siagian, Kristiani (International Journal Corner of Educational Research, 2023)
The purpose of this research is to examine the types of English sentences based on function consisting of declarative sentence, interrogative sentence, exclamatory sentence, and imperative sentence found in the folklore “Jack and The Beanstalk”. The method in this research was descriptive qualitative with research source obtained from the American Literature website. The results of this research showed that in the folklore “Jack and The Beanstalk” there were four types of English sentences based on function. Type of sentence that appeared most frequently in the folklore “Jack and The Beanstalk” was declarative sentences (46 times), followed by the exclamatory sentences (13 times). Meanwhile, the types of sentences that appeared the least were interrogative sentences (2 times) and imperative sentences (2 times). Or in percentage form, as many as 73% of the sentences in the folkore “Jack and The Beanstalk” were declarative sentences, as many as 21% were exclamatory sentences, as many as 3% were an interrogative sentences, and as many as 3% were imperative sentences.